Interviewing and change strategies for helpers - Cormier, L. Sherilyn (Thomson/Brooks/Cole, 2003)
Rev. ed. of: Interviewing strategie for helpers / Sherry Cormier, Bill Cormier. 1998; Includes bibliographical references (p. 640-672) and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)